Electrically Tunable Printed Bifocal Liquid Crystal Microlens Arrays. Issue 16 (8th June 2020) - Kamal, Waqas; Lin, Jia‐De; Elston, Steve J.; Ali, Taimoor; Castrejón‐Pita, Alfonso A.; Morris, Stephen M.
Abstract: In this communication, the fabrication of electrically tunable bifocal liquid crystal (LC) microlenses using drop‐on‐demand inkjet printing is demonstrated. By treating the glass substrate with a homeotropic alignment layer, the printed droplets are found to form plano‐convex lenses with focal lengths in the range of 220–463 µm, depending upon the number of droplets deposited at each location on the substrate. The precision of the process allows for the microlenses to be deposited in between in‐plane indium tin oxide electrodes. In the presence of a high amplitude electric field, the director within the LC droplets is observed to align with the direction of the applied field, but without any accompanying distortion in the droplet profile. However, these changes in the LC director alignment are found to result in a bifocal behavior rather than a continuous change in the focal length. It is also found that there exists a range of voltages for which two focal planes are observed. Abstract : Drop‐on‐demand printing of electrically tunable nematic liquid crystal (LC) microlenses is demonstrated. These LC microlenses are deposited precisely between in‐plane indium tin oxide electrodes and subjected to an electric field to tune the focal length. Bifocal tuning is observed for the case when the electric field direction and polarization of the incident light are colinear.